Melawan Hegemoni Golkar: Lahir dan Perkembangan PPP di Aceh Masa Orde Baru - Alfian, Alfian; Handoko, Handoko (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The New Order era in Indonesia was characterized by the hegemony of the power holders at that time. The New Order government was synonymous with Soeharto's authoritarian rule, including in politics. During his reign, Soeharto controlled power by consolidating political parties into three major parties. However, the most influential party was Golkar, which at the time of the election became the winning party in almost every province in Indonesia. Despite Golkar's hegemony, the winning party in Aceh was PPP. This article discusses the birth and development of PPP in Aceh using qualitative methods by collecting sources from various libraries and archives as well as interviews. This method was used to find out why PPP was able to resist Golkar's hegemony in Aceh and to develop and be accepted by the people of Aceh.